Edukasi Parenting dan Atlet: Pentingnya Latihan Fisik Atlet POPB Ski Air dan Wakeboard Tahun 2026 - Uzizatun Maslikah; Fahmy Fachrezzy; Iwan Hermawan; Mansur Jauhari; Viranti Citrasari; Arga Nurcahya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The success of developing young athletes is determined not only by the quality of training programs but also by parents’ understanding of the importance of structured, continuous, and developmentally appropriate physical training. Preliminary observations among athletes participating in the 2026 Continuous Sports Development Program (POPB) for Water Ski and Wakeboard revealed gaps in the understanding of parents, athletes, and coaches regarding fundamental principles of physical training, recovery strategies, nutritional support, and psychosocial assistance required to optimize athletic performance. This community engagement program aimed to enhance sports parenting literacy and improve athletes’ knowledge of the critical role of physical training in performance development and injury prevention. The program employed a participatory educational approach through seminars, interactive discussions, demonstrations of evidence-based physical training principles, and mentoring sessions involving parents, athletes, and coaches. Program effectiveness was evaluated using a pretest–posttest design to measure changes in participants’ knowledge, complemented by observations of engagement throughout the activities. The results demonstrated improved understanding of training principles, exercise periodization, warm-up and cool-down procedures, recovery strategies, nutritional requirements, and the importance of collaboration among parents, coaches, and athletes in supporting long-term athlete development. Participants also showed stronger commitment to implementing structured training support and positive parenting practices that promote sustainable athletic achievement. These findings indicate that sports parenting education is an effective strategy for strengthening the athlete development ecosystem within the 2026 POPB Water Ski and Wakeboard program through enhanced collaboration among families, coaches, and athletes.